Produktivitas Karyawan Ditinjau dari Lingkungan, Kepemimpinan dan Disiplin Karyawan Konveksi Nik’s Collection Surakarta - Sotya Diva Surya Poundra; Istiatin; Sarsono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine the influence of environmental influences, leadership and employee discipline on the productivity of Nik’s Collection Surakarta convection employees. The author uses a descriptive quantitative approach. This research will be conducted for 3 months, from October 2023 to December 2023. The population in this research is 58 employees of Konveksi NIK’S Collection Surakarta. The population was less than 100, so the researchers took all employees of Konveksi NIK’S Collection Surakarta, namely 58 employees. The sampling technique in this research used a census. Researchers used multiple linear regression analysis. The results of this research show that the environment, leadership and employee discipline simultaneously have a significant influence on the productivity of Nik’s Collection Surakarta convection employees. Based on the t test, it was found that environmental results, leadership and employee discipline had a positive and significant influence on the productivity of Nik’s Collection Surakarta convection employees.